Biomechanical comparison of inside-outside screws, cables, and regular screws, using a sawbone model - (:unkn) unknown (SPRINGER, 2005)
Our aim was to conduct a biomechanical comparison of the pull-out strengths of inside-outside (I/O) screws, cables, and bone screws to determine whether I/O screws provide greater pull-out resistance than cables or bone screws, and their effectiveness with the screw diameter. There is no remarkable biomechanical experimental study comparing the I/O technique with conventional spinal techniques. The diameter of the screw heads were also biomechanically tested to determine the optimal size that can be used. In this study, 45 blocks of 50x50x5 mm of sawbone (synthetic bone, model 1137, Pacific Research Laboratories, Vashon, WA, USA) were used as bone substitutes. Fifteen sets of 14-mm inside-outside Dynalok screws and nuts, 15 wire cables, and 15 bone screws were inserted into a separate sawbone block. An NITS Bionx materials testing machine was used to measure the load to failure of each implant. The mean values and standard deviations of each group were calculated and Student's t-test was used for comparison. The load to failure of the inside-outside screws was significantly greater than that of the cables (p<0.0000004) and the regular bone screws (p<0.000002). The results also revealed that increasing the diameter of the head of the screw also increases the resistance against the pull-out strengths. Thus, using a larger screw in occipitocervical stabilization provides safe and stable fixation of the occipital bone to the cervical spine. This study also proved that sawbone is a useful and reliable alternative to allogenic fresh cadaveric bone grafts or animal bones for certain biomechanical testing.
Keywords: biomechanics; bone screws; inside-outside screw fixation; occipitocervical fixation; sawbone; wire fixation; UPPER CERVICAL-SPINE; OCCIPITOCERVICAL INSTRUMENTATION; RHEUMATOID-ARTHRITIS; WIRE FIXATION; FUSION; ARTHRODESIS; STABILIZATION; BONE